2019
DOI: 10.1002/app.48444
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective flame‐retarded polyester diol with synergistic effects for waterborne polyurethane application

Abstract: In this article, a novel bi-reactive flame retardant (FRD) was successfully synthesized for waterborne polyurethane (WPU). The chemical structures of FRD were characterized by Fourier-transform infrared spectra and 1 H and 31 P nuclear magnetic resonance. Then, the FRD was incorporated into polyurethane backbone to prepare a series of flame-retarded WPU (FRWPU). The flammability characteristics of FRWPU were measured by limited oxygen index (LOI), UL-94, and cone calorimeter (CCT) tests. The FRPWU-7 had a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…All are stable to temperatures approaching 350°C. As might be expected, the presence of BDE‐DPP containing two phosphate groups promotes char formation (22%‐24%) to a greater extent than does the DOPO derivative (12%‐15%) 34‐37 . The thermal properties for all the blends are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…All are stable to temperatures approaching 350°C. As might be expected, the presence of BDE‐DPP containing two phosphate groups promotes char formation (22%‐24%) to a greater extent than does the DOPO derivative (12%‐15%) 34‐37 . The thermal properties for all the blends are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 74%
“…Further, DOPO should undergo decomposition to release PO radical to the gas phase to scavange combustion propagating radicals 32,33 . One of them, BDE‐DPP, contains both phosphate groups which should promote char formation and a dopyl unit to contribute to gas‐phase activity 34‐37 …”
Section: Resultsmentioning
confidence: 99%
“…29 It is caused by that phosphaphenanthrene structure in VAP produced phosphoric acid compounds during combustion, and the existence of phosphoric acid compounds was conducive to the formation of char layer. 42,43 The decomposition products containing phosphorus took part in the stage of matrix melting into char, resulting in a stable char layer containing phosphorus. 44 Correspondingly, through EDX analysis, it was found that there was phosphorus element in the char residue of EP-10, which was consistent with the results of infrared spectrum.…”
Section: Analysis On Char Residuementioning
confidence: 99%
“…The innovative IFWPU is modied at the molecular level, which overcomes interfacial incompatibility (e.g., volatilization, dissolution, migration, and exudation) and provides durable high ame-retardance. [22][23][24][25] According to the differently modied PU molecular segments, the modications of IFWPU are classied as so-, hard-, and so-co-hard segment modications. [26][27][28][29][30][31][32][33] Besides, the compositions of IFWPU are classied as one-component, twocomponent, and hyperbranched based on different components.…”
Section: Introductionmentioning
confidence: 99%